Quilombo de Jamari: Intrusão, pilhagem e dramas sociais em um território etnicamente configurado no Rio Trombetas - Santos, Juliene Pereira dos (2019)
This dissertation deals with processes of appropriation of territories occupied by traditional peoples and communities in the Amazon, by private enterprise and “acts of state”, focusing on “social dramas” and political-territorial resulting from this mode of misappropriation, legitimized by the State of Right, configuring itself in looting processes of ethnically configured territories. From the social situation faced by the quilombolas of Jamari, municipality of Oriximiná, Pará; whereas since the 1970s their territory has been “intruded” by mining projects and protected areas, including full protection; historically situates the fields of conflicts and tensions experienced by this social unit from different points of view; identifies the effects of the intervention of external agents that affect the living and working conditions of these quilombolas; characterizes the social dramas resulting from the plundering of the territory by environmental projects and mineral exploration; and finally, it analyzes the strategies currently adopted by mining companies to convince communities to accept the expansion plan under the territory for the next twenty years.